2008
DOI: 10.1111/j.1365-2559.2008.03147.x
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of RASSF1A and RARb2 gene promoter methylation in morphologically normal endometrium adjacent to endometrioid adenocarcinoma

Abstract: Promoter region methylation of RASSF1A and RARb2 genes is an early event in endometrial carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 30 publications
4
31
1
2
Order By: Relevance
“…As in our present study, RASSF1 was shown to be frequently methylated in EEC (Arafa et al 2008, Pallares et al 2008. However, where we found frequent methylation for RASSF1 in UPSC in line with Liao et al (2008) and Pallares et al (2008) found less RASSF1 methylation in UPSC (20%) than in EEC (61.5%).…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…As in our present study, RASSF1 was shown to be frequently methylated in EEC (Arafa et al 2008, Pallares et al 2008. However, where we found frequent methylation for RASSF1 in UPSC in line with Liao et al (2008) and Pallares et al (2008) found less RASSF1 methylation in UPSC (20%) than in EEC (61.5%).…”
Section: Discussioncontrasting
confidence: 47%
“…In view of the described differences in clinical, histological and molecular genetic characteristics of EEC and UPSC, we hypothesized that these differences also extend to methylation patterns. In EEC, methylation of MLH1 (Esteller et al 1999, Horowitz et al 2002, Kanaya et al 2003, RARb2 (Arafa et al 2008), RASSF1 (Arafa et al 2008) and CDKN2A (p16) (Guida et al 2009) has been suggested as early events in carcinogenesis. Many other epigenetically silenced genes have been described in EEC, such as MGMT (Furlan et al 2006), PTEN (Salvesen et al 2001, Macdonald et al 2004) and GSTP1 (Chan et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies confirmed this finding: RASSF1A promoter region was reported to be methylated, in average 74% of cases of endometrial cancer patients which was associated with diseass progression (38). In a research conducted by Arafa et al it was observed that methylated promoter occurred in 74 % of patients and was corrolated with decreased gene expression level (39). It should be noted that aberrant methylation is associated with loss of heterozygosity (LOH) in chromosome 3p that frequently occur in endometrial cancer which is related with development, recurrence and survival of cancer and significantly associated with microsatellite instability in endometrial carcinomas that could block the increasing rate of genetic abnormalities in uterine carcinogenesis (40)(41)(42).…”
Section: Discussionsupporting
confidence: 65%
“…Pallarés et al (34) 74.0 --Pijnenborg et al (41) 85.0 --Seeber et al (40) 79.0 15.0 -Arafa et al (38) 74.0 --Liao et al (39) 61.5 --Kang et al (36) 81 cervical cancer. In contrast, common risk and predisposing epidemiological and histopathological factors associated with the development of uterine carcinomas have been identified.…”
Section: Rassf1a Gstp1 Cdh1mentioning
confidence: 99%